Liver tissue remodeling following ablation with irreversible electroporation in a porcine model - Monleón, Eva; Lucía, Óscar; Güemes, Antonio; López-Alonso, Borja; Arribas, Dolores; Sarnago, Héctor; Hernaez, Alba; Burdío, José Miguel; Junquera, Concepción (Frontiers in Veterinary Science, 2022)
Irreversible electroporation (IRE) is a method of nonthermal focal tissue ablation characterized by irreversibly permeabilizing the cell membranes while preserving the extracellular matrix. This study aimed to investigate tissue remodeling after IRE in a porcine model, especially focusing on the extracellular matrix and hepatic stellate cells. IRE ablation was performed on eleven female pigs at 2000 V/cm electric field strength using a versatile high-voltage generator and 3 cm diameter parallel-plate electrodes. The treated lobes were removed during surgery at 1, 3, 7, 14, and 21 days after IRE. Tissue remodeling and regeneration were assessed by histopathology and immunohistochemistry. Throughout the treated area, IRE led to extensive necrosis with intact collagenous structures evident until day 1. From then on, the necrosis progressively diminished while reparative tissue gradually increased. During this process, the reticulin framework and the septal fibrillar collagen remained in the necrotic foci until they were invaded by the reparative tissue. The reparative tissue was characterized by a massive proliferation of myofibroblast-like cells accompanied by a complete disorganization of the extracellular matrix with the disappearance of hepatic architecture. Hepatic stellate cell markers were associated with the proliferation of myofibroblast-like cells and the reorganization of the extracellular matrix. Between 2 and 3 weeks after IRE, the lobular architecture was almost completely regenerated. The events described in the present study show that IRE may be a valid model to study the mechanisms underlying liver regeneration after extensive acute injury.